Estimating human leishmaniasis burden in Spain using the capture-recapture method, 2016-2017. - Ana María Humanes-Navarro (Public Library of Science (PLoS), 2021)
Leishmaniasis is endemic and a mandatory reporting disease in Spain since 1982. However, between 1996 and 2014, surveillance on public health was decentralized and only some autonomous regions monitored the disease. The aim of this study is to estimate the incidence of leishmaniasis and to evaluate the extent of underreporting in Spain. A capture-recapture (CRC) study was conducted to calculate the incidence of human leishmaniasis using reports from the National Surveillance Network (RENAVE) and the Hospital Discharge Records of the National Health System (CMBD) for 2016 and 2017. During the study period, 802 cases were reported to RENAVE and there were 1,149 incident hospitalizations related to leishmaniasis. The estimated incidence rates through the CRC study were 0.79 per 100,000 inhabitants for visceral leishmaniasis (VL), 0.88 (cutaneous leishmaniasis (CL)) and 0.12 (mucocutaneous leishmaniasis (MCL)) in 2016 and 0.86 (VL), 1.04 (CL) and 0.12 (MCL) in 2017. An underreporting of 14.7-20.2% for VL and 50.4-55.1% for CL was found. The CRC method has helped us to assess the sensitivity and representativeness of leishmaniasis surveillance in Spain, being a useful tool to assess whether the generalization of leishmaniasis surveillance throughout the Spanish territory achieves a reduction in underreporting.